Variability in Winter Wheat (Triticum aestivum L.) Grain Yield Response to Nitrogen Fertilization in Long-Term Experiments - Omara, Peter; Aula, Lawrence; Dhillon, Jagmandeep S.; Oyebiyi, Fikayo; Eickhoff, Elizabeth M.; Nambi, Eva; Fornah, Alimamy; Carpenter, Jonathan; Raun, William (Communications in Soil Science and Plant Analysis, 2020)
Crop nitrogen (N) use is always affected by the variability in production environment. Dataset (2001 to 2014) from long-term winter wheat (Triticum aestivum L.) experiments at Lahoma and Stillwater, Oklahoma was used. Both experiments have a randomized complete block design with four replications, and fertilizer N was applied as urea pre-plant. Responsiveness of grain yield to maximum fertilizer N rate (112 kg ha−1 – Lahoma; 135 kg ha−1 – Stillwater) was compared with that from check plot (0 kg ha−1). The objective was to determine the relative influence of environment, management, and variety on winter wheat grain yield. The combined analysis of variance indicated that the main effect of year, treatment, location, and variety accounted for 29.3%, 21.2%, 3.1%, and 22.6%, respectively of the variance terms. Over the study period, the nonresponsiveness of winter wheat to fertilizer N accounted for 29% and 23% of grain yield at Lahoma and Stillwater, respectively where yield at maximum N rate did not significantly differ from check plot. This highlights the importance of random changes in a crop production environment and its influence in dictating the response to applied N fertilizer. Nitrogen fertilizer losses could be reduced by adopting in-season variable N application techniques.
Keywords: Winter wheat; Variability; Nitrogen fertilization; Grain yield response